Piezoelectric Signals in Vascularized Bone Regeneration - Delfo D’Alessandro (MDPI AG, 2021)
The demand for bone substitutes is increasing in Western countries. Bone graft substitutes aim to provide reconstructive surgeons with off-the-shelf alternatives to the natural bone taken from humans or animal species. Under the tissue engineering paradigm, biomaterial scaffolds can be designed by incorporating bone stem cells to decrease the disadvantages of traditional tissue grafts. However, the effective clinical application of tissue-engineered bone is limited by insufficient neovascularization. As bone is a highly vascularized tissue, new strategies to promote both osteogenesis and vasculogenesis within the scaffolds need to be considered for a successful regeneration. It has been demonstrated that bone and blood vases are piezoelectric, namely, electric signals are locally produced upon mechanical stimulation of these tissues. The specific effects of electric charge generation on different cells are not fully understood, but a substantial amount of evidence has suggested their functional and physiological roles. This review summarizes the special contribution of piezoelectricity as a stimulatory signal for bone and vascular tissue regeneration, including osteogenesis, angiogenesis, vascular repair, and tissue engineering, by considering different stem cell sources entailed with osteogenic and angiogenic potential, aimed at collecting the key findings that may enable the development of successful vascularized bone replacements useful in orthopedic and otologic surgery.